Dynamics of the Natural Regeneration of Vegetation in an Anthropized Forest in Côte d’Ivoire, West Africa - Kouame Jean Marc Kouman; Akoua Tamia Madeleine Kouakou; Kouassi Bruno Kpangui; Issouf Bamba; Yao Sadaiou Sabas Barima; Jan Bogaert (Ecologies, 2022)
Ivorian classified forests have been highly anthropized by cocoa farming. In an attempt to provide guidance to the government on approaches to the restoration of the forest while respecting the aspirations of local populations, permanent plots were set up in the classified forest of Haut-Sassandra, and were monitored and measured for 3 years. This study was intended to analyze the evolution of the vegetation of permanent plots in the classified forest of Haut-Sassandra from 2018 to 2021. The results show that the vegetation evolves with the cessation of some agricultural activities. These plantations are colonized by pioneer species during the first three years of the abandonment of agricultural activities. Mortality rates increased by 477.59% and recruitment rates were reduced by 61.87% in regularly maintained plantations compared to their condition three years ago. However, the plantations with no agricultural activities and those which were not maintained but harvested had the highest recruitment rates of pioneer and heliophilous individuals. In sum, tree species could recolonize the classified forest of Haut-Sassandra if clearing is prohibited in cocoa farms. However, the populations could continue to harvest the pods from the cocoa trees which are already established in the classified forest of Haut-Sassandra.